Antidepressants for the treatment of depression in neurological disorders: a systematic review and meta-analysis of randomised controlled trials. Issue 8 (10th May 2011) - Price, Annabel; Rayner, Lauren; Okon-Rocha, Ewa; Evans, Alison; Valsraj, Koravangattu; Higginson, Irene J; Hotopf, Matthew
Abstract : Background: Despite the high prevalence of depression in people with neurological disorders, no previous study has sought to summarise existing evidence on the use of antidepressants in this population. A systematic review and meta-analysis was undertaken to determine whether antidepressants are more effective than placebo in the treatment of depression in neurological disorders, and whether any benefit is associated with improvement in function. Methods: Embase, Pubmed, Psycinfo and Cochrane trial registers were searched for randomised controlled trials (RCTs) comparing the efficacy of antidepressant and placebo in the treatment of depression in adults with a neurological disorder. Findings: 20 RCTs were included in the review, including patients with Parkinson's disease, multiple sclerosis, brain injury, epilepsy and stroke. Outcomes were analysed at four time points: 4–5 weeks, 6–8 weeks, 9–18 weeks and >18 weeks. The primary outcome was response to treatment at 6–8 weeks. The evidence favoured the use of antidepressants over placebo at all time points although pooled results were not statistically significant at all time points. At 6–8 weeks, antidepressant treatment was associated with a greater than twofold odds of remission (OR 2.23; 95% CI 1.54 to 3.23; number needed to treat=7). Fewer data were available for quality of life, and functional and cognitive outcomes, and there was little evidence of improvement with antidepressant treatment. Interpretation: Antidepressants are effective for the treatment of depression in patients with neurological disorders but the evidence for the efficacy of antidepressants in improving quality of life, and functional and cognitive outcomes is inconclusive.